Challenges in the Assessment of Bycatch: Postmortem Findings in Harbor Porpoises (Phocoena phocoena) Retrieved From Gillnets. Issue 2 (March 2021) - IJsseldijk, Lonneke L.; Scheidat, Meike; Siemensma, Marije L.; Couperus, Bram; Leopold, Mardik F.; Morell, Maria; Gröne, Andrea; Kik, Marja J. L.
Bycatch is considered one of the most significant threats affecting cetaceans worldwide. In the North Sea, bottom-set gillnets are a specific risk for harbor porpoises ( Phocoena phocoena ). Methods to estimate bycatch rates include on-board observers, remote electronic monitoring, and fishermen voluntarily reporting; none of these are systematically conducted. Additionally, necropsies of stranded animals can provide insights into bycatch occurrence and health status of individuals. There are, however, uncertainties when it comes to the assessment of bycatch in stranded animals, mainly due to the lack of diagnostic tools specific for underwater entrapment. We conducted a literature review to establish criteria that aid in the assessment of bycatch in small cetaceans, and we tested which of these criteria applied to harbor porpoises retrieved from gillnets in the Netherlands ( n = 12). Twenty-five criteria were gathered from literature. Of these, "superficial incisions, " "encircling imprints, " and "recent ingestion of prey" were observed in the vast majority of our confirmed bycatch cases. Criteria like "pulmonary edema, " "pulmonary emphysema, " and "organ congestion" were also frequently observed, although considered unspecific as an indicator of bycatch. Notably, previously mentioned criteria as "favorable health status, " "absence of disease, " or "good nutritional condition" did not apply to the majority of our bycaught porpoises. This may reflect an overall reduced fitness of harbor porpoises inhabiting the southern North Sea or a higher chance of a debilitated porpoise being bycaught, and could result in an underestimation of bycatch rates when assessing stranded animals.